Relationship between the vertical occlusal dimension and facial biotype in 3, 4 and 5 year-old children - Araujo Ramirez, Martha (2021)
Objective: To determine the relationship between the vertical occlusal dimension and the facial biotype in 3, 4- and 5-year-old children of the kindergarten N.° 591 Carlos Manuel Cox, in 2019. Methods: The study used a non-experimental and cross-sectional design. The sample was carried out through a non-probabilistic sampling for consecutive cases and was comprised of 62 children who met the inclusion and exclusion criteria. The children were examined in a position of maximum intercuspation, recording the measurements of the subnasal to chin point, facial height (ofrion-gnation) and facial width (bizygomatic distance) using a digital caliper. The statistical analysis was performed in the SPSS v21 program. Results: The average vertical dimension was found to be 54.11 ± 2.99 mm. Children with a dolichofacial biotype had a greater occlusal vertical dimension with a value of 55.45 ± 2.80 mm. It was evidenced that the relationship between the facial biotype and the measurements of the occlusal vertical dimension were statistically signiﬁcant (p = 0.006). Conclusion: There is a relationship between the facial biotype and the vertical occlusal dimension, which indicates that diﬀerent facial shapes have characteristics associated with the length of the lower third of the face.